And Beauty Will Make You Free: On the Transformative Power of Beauty - Pavol Bargár (Acta Universitatis Carolinae Theologica, 2023)
In allusion to the famous Johannine dictum, this paper seeks to explore the relationship between beauty and liberation. Liberation is here understood in terms of a movement toward transforming all reality in accordance with the principles of the coming reign of God, ‘so that God may be all in all’ (1 Cor 15:28). Complementarily, beauty is not interpreted merely as a matter of taste and preference but as something that permeates all dimensions of being human. The paper, therefore, argues that beauty not only gives expression to the human yearning for transformation but that both beauty and liberation represent the constitutive elements of Christian praxis. Thus, beauty provides a framework through which the current reality can not only be seen but also discerned, experienced, and performed in a new way, thus effectively opening up possibilities for transformation as God’s project of inaugurating a new heaven and a new earth. Therefore, it will be proposed that beauty represents a key theme for theological reflection (locus theologicus), having aesthetic, ethical, and ontological implications for Christian theology. This point will not only be discussed in conversation with various theological voices but also illustrated through engagement with cinema, namely, Jane Campion’s The Power of the Dog.